Service Supervision in Improving the Spirit of Serving Servants - Parlaungan Nainggolan; Andar Gunawan Pasaribu (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Effective ministry in the church is highly dependent on the spirit and dedication of the servants. However, in practice, many servants experience boredom, loss of motivation, and lack of direction in ministry. This study aims to examine the role of ministry supervision as a strategic tool in increasing the spirit of ministry of servants in the church environment. Through a qualitative approach with literature studies and contextual observations, it is discussed that supervision carried out with a nurturing, communicative, and empowering leadership approach can revive enthusiasm, responsibility, and commitment to ministry. Supervision is not just administrative supervision, but a pastoral action that touches on the spiritual and emotional aspects of the servant. The results of the study show that effective supervision plays a role in forming a healthy and sustainable ministry culture, as well as increasing awareness of the divine calling in every act of service. This study recommends a dialogical, reflective, and participatory supervision model as a strategic step in fostering faithful and enthusiastic servants.